2020
DOI: 10.3390/polym12071540
|View full text |Cite
|
Sign up to set email alerts
|

The Buffer Effect of Different Wood Species and the Influence of Oak on Panel Composites Binders

Abstract: The buffer action of certain wood species can intensely affect the curing and hardening of some thermosetting wood adhesives. The present article presents a quantification of such buffering effects, determined under controlled conditions, in various wood species. The buffer capacity of oak has been found to be rather extreme and is likely to affect quite heavily the ability of urea-formaldehyde (UF) and melamine-urea-formaldehyde (MUF) wood panel adhesives in industrial operations. A variation of the buffer ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…An average of 97 kJ/mol was observed for all conversions from 10% to 90 % of SS, which is close to the 104 kJ/mol calculated from the Kissinger model (Table ). The curing kinetics of thermosets tend to be complex in the presence of wood due to the chemical components present and buffering capacity of wood, but the plots of E a at different α can provide an understanding of the energy changes within the system as temperature increases . With the addition of 50 wt % 40-mesh wood fiber, E a showed a significant increase from 28 kJ/mol (40% α) to 73 kJ/mol (90% α) (Figure e).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An average of 97 kJ/mol was observed for all conversions from 10% to 90 % of SS, which is close to the 104 kJ/mol calculated from the Kissinger model (Table ). The curing kinetics of thermosets tend to be complex in the presence of wood due to the chemical components present and buffering capacity of wood, but the plots of E a at different α can provide an understanding of the energy changes within the system as temperature increases . With the addition of 50 wt % 40-mesh wood fiber, E a showed a significant increase from 28 kJ/mol (40% α) to 73 kJ/mol (90% α) (Figure e).…”
Section: Resultsmentioning
confidence: 99%
“…The curing kinetics of thermosets tend to be complex in the presence of wood due to the chemical components present and buffering capacity of wood, but the plots of E a at different α can provide an understanding of the energy changes within the system as temperature increases. 38 With the addition of 50 wt % 40-mesh wood fiber, E a showed a significant increase from 28 kJ/mol (40% α) to 73 kJ/mol (90% α) (Figure 2e). A similar increase in E a was observed with 60 wt % wood around 40% α.…”
Section: Modulated Dynamic Scanning Calorimetry (Mdsc)mentioning
confidence: 96%
“…Another potential factor that could lower the IB reading for LL is the fact that it has higher buffering. The buffering slows down curing, especially when using MUF as a binder (Policardi and Thebault 2020). The significant IB reduction once the LL had been added indicates the need to modify the resin cures time prior to bonding.…”
Section: Effects Of Species and Mixingmentioning
confidence: 99%
“…Additional properties of buffer capacity and chemical composition of the wood was also looked at. Buffering capacities but has been shown to impact resin behaviour during curing process (Policardi and Thebault 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Policardi and Thebault [ 17 ] evaluated the buffer capacities of eight wood species in particleboard production. It was found that the buffer capacity of oak wood was rather extreme and concluded that it is possible to affect the ability of both melamine-urea formaldehyde and pure formaldehyde resin in industrial operation.…”
mentioning
confidence: 99%